PENGEMBANGAN DESA WISATA KREATIF KENEP SUKOHARJO BERBASIS PEMBERDAYAAN MASYARAKAT - Rosita Dwiana Prayudawisi; Pudji Astuti (Journal of Politic and Government Studies, 2019)
The purpose of this research are to explain the society participation in the realization of the development Creative Tourism Village of Kenep, the empowerment activities, the obstacles and the solutions in developing the Creative Tourism Village based on community empowerment. The type of this research is descriptive analytic using qualitative approach. The data source in this research is obtained from interviewing informant and collecting archives or documents that is related to this study. In collecting the data, the writer uses interview, observation, and documentation technique. In analyzing the data, the writer uses collecting data, selecting data, presenting data and making a conclusion technique. The validation data uses source triangulation technique. According to the result of this research, we can know that the society participation in the realization of the development Creative Tourism Village of Kenep is started from the aid of Empowerment in Urban Areas (PNPM-Urban) that showed ideas from society to explore and examine the potencies in Kenep. The Villagers identify and examine the potential areas, problems and opportunities in Kenep, arrange the pokdarwis activities plan of the community involving them in training to increase their potencies maximally. The Villagers have an initiative and creativity to develop this Creative Tourism Village. The community empowerment are, for example, training how to make a batik, rambag, or another home industry by the owner directly to increase the economy of local society. The community empowerment also decrease the number of urbanization because it creates jobs and makes the area known by wide community. The villagers are involved in accompaniment activities to explore the potencies of Kenep. They are also involved in promoting and holding a festival to attract the visitors. There are some obstacles in developing the Creative Tourism Village of Kenep Sukoharjo. The community are lack of participation. They do not want to intervene because of the assumption that there are particular people managing the village. Some villagers do not really understand what tourism village is. There are some villagers thinking that they are not involved. The capital, the facilities, infrastructure and the human resources are limited. The management of the tourism village is still traditional. There is no record book to note the number of visitors and the amount of income. The packaging and the marketing of the products are not optimal. Resolving the obstacles, the village socialization activities about community empowerment have to be optimized. The involved stakeholder have to create a good and intensive communication. The society have to provide good and competent human resources to manage the Creative Tourism Village of Kenep. If the Creative Tourism Village of Kenep can be managed maximally so it will give positive influence that is increasing the economy of the local community.Keywords: Community Empowerment, Development, Tourism Village.